Distribution characteristics of colorectal cancer patients for gender and age depending of hereditary predisposition to the disease - Lozynska, M.R.; Fedota, O.M.; Lozynska, L.Yu.; Prokopchuk, N.M.; Pinyazhko, R.O. (Онкологія, 2016)
Aim: to analyze the distribution of males and females by the age of colorectal cancer (CRC) onset with and without hereditary predisposition to the disease to identify individuals at risk group. Subjects and methods: the medical records and the genealogical information of 182 patients with CRC were analyzed, including 94 males and 88 females. «Positive» familial anamnesis for CRC was confirmed in 61 probands: 40 patients to met 1–2 of Amsterdam criteria for Lynch syndrome, 9 patients to met 3 Amsterdam criteria, 7 patients had familial adenomatous polyposis, 3 patients had familial CRC-associated inflammatory bowel diseases, 1 patient had MUTYH-associated polyposis, 1 patient had Peutz — Jeghers syndrome. Results: age manifestation of the disease varied in regarding patient’s gender and family history. In probands with «positive» familial anamnesis for CRC the peak age of the disease onset was 5 years lower for both genders, compared to the age of individuals without family history. The average age of CRC onset in probands of both genders with «positive» familial anamnesis for this disease was the statistically significant lower, than in patients without family history. The statistically significant difference for the average age of the CRC manifestation between males and females without family history was revealed. Conclusion: thus, the study of gender and age-CRC is one of the urgent problems of modern medicine. A precise understanding age of inherited CRC manifestation of patients with CRC is important for identifying at-risk individuals, improving cancer surveillance and prevention strategies, and developing better diagnostic and therapeutic approaches.